Consumer Behavior in the Digital Era: A Meta Review (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study investigates the impact of artificial intelligence (AI) on consumer behavior in the digital era, with a particular focus on the Nepalese context. It aims to explore how AI influences consumer decision-making, adoption patterns, and perceptions across digital channels.Methods: A systematic meta-review was conducted using peer-reviewed and grey literature published between 2015 and 2024. Studies were selected based on PRISMA guidelines, emphasizing empirical research on AI-driven personalization, marketing, privacy, and ethics. Data extraction and thematic synthesis were performed to identify prevailing trends and gaps.Results: The review reveals that AI enhances consumer experiences through personalized recommendations, predictive analytics, and real-time assistance. However, concerns regarding privacy, algorithmic bias, and ethical transparency persist. Factors such as perceived usefulness, ease of use, trust, and social influence significantly shape AI adoption. Contextual variables like generational differences and cultural norms also impact consumer behavior.Conclusion: AI is reshaping consumer behavior by delivering personalized experiences, predictive insights, and real-time engagement. To enhance consumer adoption, priority should be given to factors such as perceived usefulness, ease of use, trustworthiness, and ethical transparency. Social influence and cultural sensitivity also play pivotal roles, especially in emerging markets like Nepal. Future research should focus on optimizing these determinants to bridge socio-technical gaps and foster inclusive, responsible AI integration.